2019
DOI: 10.3390/agronomy9080445
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite-Targeted Analysis and Physiological Traits of Zea mays L. in Response to Application of a Leonardite-Humate and Lignosulfonate-Based Products for Their Evaluation as Potential Biostimulants

Abstract: The main aim of this study is to identify and investigate specific humates (Hs) as potential biostimulants. Five specialty lignosulfonates (LS1-5), one commercial leonardite-humate (PH), and one commercial lignosulfonate (LH), were analyzed for their carbon, nitrogen, and sulfur contents, and the distribution of functional groups using Fourier transform infrared (FTIR) and Raman spectroscopies. Hs were further supplied for two days to Zea mays L. in hydroponics to test their capacity to trigger changes in phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 45 publications
2
23
0
1
Order By: Relevance
“…Elevated contents of photosynthetic pigments are known to positively correlate with the photosynthetic process in plants, which is responsible for the production of photosynthates contributing to plant growth. Consistently with our findings, higher SPAD (Soil Plant Analysis Development) values, which are indicative of higher chlorophyll content in plants, and enhanced Rubisco activity and sugar production were previously observed in maize plants treated with lignohumates [53]. The same HS from earthworm coprolites of FM and FMM soils also improved plant nutrition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Elevated contents of photosynthetic pigments are known to positively correlate with the photosynthetic process in plants, which is responsible for the production of photosynthates contributing to plant growth. Consistently with our findings, higher SPAD (Soil Plant Analysis Development) values, which are indicative of higher chlorophyll content in plants, and enhanced Rubisco activity and sugar production were previously observed in maize plants treated with lignohumates [53]. The same HS from earthworm coprolites of FM and FMM soils also improved plant nutrition.…”
Section: Discussionsupporting
confidence: 92%
“…HS have been additionally reported to stimulate plant growth by targeting pivotal pathways of plant metabolism, primarily nitrogen assimilation [52][53][54]. The activity of the nitrogen assimilation enzyme GS, was more increased by HS extracted from earthworm coprolites collected in FM, likely because of higher N uptake and accumulation by plants.…”
Section: Discussionmentioning
confidence: 99%
“…This field includes increasing plant growth and development efficiency, e.g., increasing yield, enhancing crop quality, increasing plant tolerance to and recovery from abiotic stresses, facilitating nutrient assimilation, translocation and use, enhancing the quality of produce, enabling more efficient water utilization, and enhancing certain physicochemical properties of the soil (Calvo et al 2014). However, the mechanisms activated by biostimulants are often difficult to identify and are still under investigation (Rouphael et al 2015;Nardi et al 2016;Ertani et al 2019;Paul et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ertani et al [27] carried out a short-term trial on hydroponically grown maize to assess the physiological responses to leonardite-humate-and lignosulfonate-based biostimulants. The biostimulants application in particular lignosulfonates boosted root and leaf growth by 51-140% and 5-35%, respectively.…”
Section: The Role Of Non-microbial and Microbial Biostimulants In Mormentioning
confidence: 99%
“…The biostimulants application in particular lignosulfonates boosted root and leaf growth by 51-140% and 5-35%, respectively. The authors concluded that a putative mechanism involved in the biostimulant action of these products might be the stimulation of N metabolism in the belowground organs (i.e., roots) according to the increased activity of key enzymes such as glutamine synthetase and glutamate synthase [27]. Moreover, Kim et al [28], elucidated the hormonal effects of a commercial vegetal-based biostimulants containing amino acids, lateral root promoting peptide, lignosulfonates and micronutrients on cuttings of basil, tomato and chrysanthemum, characterized by different relative root ability: easy, moderate and difficult, respectively.…”
Section: The Role Of Non-microbial and Microbial Biostimulants In Mormentioning
confidence: 99%